Kontribusi Brand Image, Online Customer Review Terhadap Purchase Decision Pada Marketplace Shopee - Galih Raspatih; Umban Adi Jaya; Yuyun Yuniati Yuningsih (PT Naureen Digital Education, 2023)
The purpose of this research is to analyze the contribution of brand image variables, online customer reviews to buying decisions in the Shopee market. The population of this study were buyers at the shopee market with a sample of 100 respondents and was determined using a non-rational sampling technique. Primary data was obtained with the help of a questionnaire, while secondary data was used in the literature. Based on the results of the SPSS version 26.0 test which is said to be a search tool test, all indicators are valid and all variables are reliable. Based on the F-test, all independent variables simultaneously influence purchasing decisions. Based on the regression coefficient and the test results show that brand image has a positive and significant effect on Purchase Decision